A Differentiated Approach to the Assessment of Biomarkers Depending on the Phenotype of Heart Failure - Nadiia M. Kulaiets (Ukrainian Journal of Cardiovascular Surgery, 2025)
Heart failure (HF) remains a major cause of hospitalization and mortality globally. Current evidence suggests significant differences in cardiovascular outcomes based on ejection fraction (EF) phenotypes, including HF with reduced (HFrEF), mildly reduced (HFmrEF), and preserved (HFpEF) EF. Biomarkers such as NT-proBNP, BNP, ST2, and Galectin-3 provide valuable insight into myocardial remodeling and inflammation. However, the prognostic role of their ratios across different HF phenotypes remains unclear.Aim. To determine the prognostic value of NT-proBNP, BNP, ST2, Galectin-3, and their ratios in patients with HF categorized by EF (HFrEF, HFmrEF, and HFpEF), regarding rehospitalization and one-year mortality risk.Materials and Methods. A prospective study including 398 patients (aged 45–65 years) hospitalized for decompensated HF. Patients were classified into three groups: HFrEF (≤40%, n=167), HFmrEF (41–49%, n=133), and HFpEF (≥50%, n=98). Biomarker levels were measured via enzyme-linked immunosorbent assay (ELISA), and the primary outcomes were HF-related rehospitalization and one-year mortality.Results. Patients with HFrEF had a significantly higher frequency of NYHA class IV (21.0%, p=0.0001), atrial fibrillation (70.1%, p=0.0001), and one-year mortality (12.0%, p=0.0001) compared to those with HFmrEF or HFpEF. HFrEF patients also had higher NT-proBNP levels (+16.2%, p=0.015) and ST2 levels (43.0 [38.3–47.3] ng/mL, p=0.004). Rehospitalization risk in HFrEF increased with NT-proBNP >843.0 pg/mL (OR=1.82, 95% CI: 1.37–2.41, p<0.0001) and NT-proBNP/ST2 >21.61 (p<0.0001). Among HFmrEF and HFpEF patients, elevated BNP (≥86.18 pg/mL, p=0.019) and Galectin-3 (>2.15 ng/mL, p=0.0047) were significant predictors of rehospitalization. In patients with HF and atrial fibrillation (AF) (n=226), compared to those with sinus rhythm (n=172), there were more cases of advanced NYHA class (III–IV) and higher mortality. Additionally, AF was associated with elevated NT-proBNP, ST-2 and galectin-3, suggesting a more severe clinical course and worse prognosis.Conclusions. Different HF phenotypes exhibit distinct biomarker profiles associated with rehospitalization and mortality risk. NT-proBNP/ST2 and NT-proBNP/BNP ratios have high prognostic value in HFrEF, whereas BNP and Galectin-3 are more predictive in HFmrEF and HFpEF. These findings highlight the importance of phenotype-specific biomarker assessment for personalized HF management.